Reinstatement of memory representations for lifelike events over the course of a week. Issue 1 (December 2017) - Oedekoven, Christiane; Keidel, James; Berens, Sam; Bird, Chris
Abstract When we remember an event, the content of that memory is represented across the brain. Detailed memory retrieval is thought to involve the reinstatement of those representations. Functional MRI combined with representational similarity analyses (RSA) of spatial patterns of brain activity has revealed reinstatement of recently-experienced events throughout a core memory retrieval network. In the present study, participants were scanned while they watched, immediately retrieved and then retrieved after a week, 24 short videos. Following the delayed retrieval, they freely recalled all videos outside of the scanner. We observed widespread within- and between-subject reinstatement effects within a posterior midline core memory retrieval network during all phases of the experiment. Within precuneus, bilateral middle temporal gyrus and the left hippocampus, reinstatement effects between the retrieval phases correlated with memory performance. These findings extend previous studies that have only employed short retention periods or highly rehearsed materials, demonstrating that memory representations for unique events are reliably reinstated over longer timeframes that are meaningful in the context of real-world episodic memory.